The Effects of Environmental Noise on Annoyance, Stress, and Urine Cortisol Levels Among Residents Living Near Industrial Sites in Bangkok, Thailand - Onmek, Nutthajit; Bordeerat, Narisa Kengtrong; Wangwongwatana, Supat (UI Scholars Hub, 2024)
People are exposed to environmental noise each day. It may be annoying, cause stress, induce hormonal changes, and negatively affect long-term health. This study aimed to determine the effects of environmental noise on annoyance, perceived stress, stress symptoms, and urine cortisol in people living in a selected area. This cross-sectional study was conducted from April to October 2022 on 142 participants. Urine samples were collected to determine cortisol levels, and perceived stress, stress symptoms, and environmental noise annoyance were evaluated using questionnaires. Stress symptoms correlated with traffic, industrial, and community noise, but not aircraft noise. Community noise correlated most strongly with all stress symptoms. Only community noise exposure was correlated with perceived stress. People reported that industrial and community noise affected their health and daily activities. Cortisol correlated with only traffic noise annoyance. Environmental noise was associated with stress symptoms and stress hormones. In brief, sound level is not the onlyindicator of stress or health impacts, but annoyance and concern over the effects of noise may negatively affect stress and health.